Students’ Anxieties Toward Their Negative Evaluation and Mistakes in Task Completion - Misdi Misdi; Diana Rahmawati Rozak; Qori Safira (Universitas Cokroaminoto Palopo, 2022)
This paper reports anxieties experiences in tasks completion in speaking activities. Following exploratory case study, the study took place at a private university in Indonesia. Three female EFL university students were recruited and participated in the research project based on the voluntarily basis principle. In garnering the data, journal reflection and interview were employed to evaluate participants’ sense of anxieties toward the speaking project. The findings reveal the students’ anxieties occurred during the English speaking because lack of preparation. At the end, research implication and recommendation are presented and discussed